Self-filling enclosures to experimentally assess plankton response to pulse nutrient enrichments. (13th January 2023) - Giménez-Grau, Pau; Camarero, Lluís; Palacín-Lizarbe, Carlos; Sala-Faig, Marc; Zufiaurre, Aitziber; Pla-Rabés, Sergi; Felip, Marisol; Catalan, Jordi
Abstract: Experimental nutrient additions are a fundamental approach to investigating plankton ecology. Possibilities range from whole-lake fertilization to flask assays encompassing a trade-off between closeness to the "real world" and feasibility and replication. Here we describe an enclosure type that minimizes the manipulation of planktonic communities during the enclosure filling. The enclosure (typically ~100 L volume) consists of a narrow translucent cylinder that can comprise the entire photic zone (or a large part of it in clear deep lakes, e.g. 20-m long) and holds a sediment trap at the bottom for recovering the sinking material. The enclosures are inexpensive and straightforward to build. Thus, many can be used in an experiment, favoring the diversity of treatments and the number of replicates. They also are lightweight with easy transport and use in lakes that cannot be reached by road. The enclosures are fundamentally aimed at investigating the short-term response of the planktonic community, integrated across the photic zone, to pulse perturbations using before and after comparisons and multiple replication and treatments. The pros and cons of the enclosure design are evaluated based on experience gained in Lake Redon, a high mountain ultraoligotrophic deep lake in the Pyrenees.